Longevity of Bipolaris oryzae on HEERA-2 Hybrid Rice Seed (Journal of Environmental Science and Natural Resources, 2021)
Seeds of hybrid rice variety Heera-2 was collected from Mymensingh district in Bangladesh. Longevity of Bipolaris oryzae was studied in 2012 to 2016 at Seed Pathology Centre, Bangladesh Agricultural University, Seed processing &preservation center and Seed Pathology Laboratory of Supreme Seed Company Limited. The data collected from the experiments were analyzed for test of significance and compared the treatment means by using DMRT at 5% level of probability following the Statistical tool for Agricultural Research (STAR) 2.1 program.The longevity of B. oryzae was observed till five years by blotter incubation methods, seedling symptom test and growing on test. Both untreated and seeds treated with Vitaflo 200FF (carboxin and thiram) were kept in jute bag and polybag stored for five years under both normal and dehumidified condition. The inocula of B. oryzae on Hybrid Heera 2 seed remained viable up to five years. When the seed samples were stored under dehumidified condition, the highest incidence of B. oryzae was recorded in case of jute bag after five years. After treated with Vitaflo 200FF, there was no any infection of B. oryzae under both storage conditionEnviron. Sci. & Natural Resources, 12(1&2): 209-213, 2019